Increasing student resilience with strength-based group counseling - Ramadhoni, Sri Rahmah; Lubis, Putri Rahmi Virani; Santera, Teri; Adiyatma, Rizki; Azizah, Nurul; Rimonda, Rubi (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2024)
The challenges faced by students, such as managing time between studies, developing social networks, and determining and building a career, are academic and non-academic demands that students have to go through at school, which can be a disturbance to psychological well-being. Therefore, a counseling service such as strength-based group counseling is very important to strengthen students' positive character. By knowing this character, interventions related to developing resilience will be more targeted. This research aims to determine the effectiveness of strength-based group counseling to increase student resilience. This research method uses a pretest and multiple posttest designs. The purposeful sampling technique was used to select 14 experimental student subjects who were placed into two groups randomly, so that each group consisted of seven students from SMA Negeri 5, Semarang City, Indonesia. Data collection using the Connor Davidson Resilience Scale was adjusted to the characteristics of the research subjects. Data analysis used repeated measures ANOVA. The results of the mixed repeated measures ANOVA test show that strength-based group counseling is effective in increasing student resilience. Furthermore, there is an interaction effect between time and group. These findings confirm that strength-based group counseling is effective and can be applied to increasing student resilience